(untitled) (Bangladesh Veterinarian, 2014)
Anaesthetic trials were conducted with propofol (P), xylazine-propofol (XP), xylazine-ketamine (XK), xylazine-thiopentone (XT) in 16 healthy indigenous pigs. Respiration rate decreased significantly (P < 0.01) five minutes after induction, and during maximum depth of anaesthesia, and had not returned to control value after recovery from anaesthesia with all anaesthetic combinations. Heart rate with P increased significantly (P<0.01) five minutes after induction, whereas it decreased significantly (P < 0.01) with XP, XK and XT during anaesthesia and remained below the normal range after recovery from anaesthesia except after XP. In all anaesthetic sessions, rectal temperature decreased significantly (P < 0.01) in all stages of anaesthesia: after recovery the rectal temperature almost returned to control value in P and XP. Slight to moderate salivation was observed in all pigs with P and XP. It is suggested that P and XP combination seems to be suitable for general anaesthesia in pigs, but XP is more suitable. DOI: http://dx.doi.org/10.3329/bvet.v30i2.18254 Bangl. vet. 2013. Vol. 30, No. 2, 46-53